2019
DOI: 10.1136/bcr-2018-229033
|View full text |Cite
|
Sign up to set email alerts
|

“I am not delusional!” Sensory dysaesthesia secondary to degenerative cervical myelopathy

Abstract: Degenerative cervical myelopathy (DCM) is the most common cause of adult spinal cord dysfunction, most classically presenting with a broad-based gait and clumsy hands. Limb sensory loss and paraesthesia are considered common symptoms of DCM. However, we report an unusual case of a patient presenting with prominent and atypical sensory symptoms. The patient repeatedly presented to accident and emergency complaining of her body resembling a wet gel-like substance that she attributed to the use of olive oil moist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Kobayashi et al found that DCM patients reported chest tightness 22.9 times more often than non-myelopathic patients, 73 resulting in inclusion as one of the symptoms to be queried in an 8-item questionnaire for DCM screening. Mowforth et al 74 reported a patient with sensory dysesthesia, including facial dysesthesia secondary to DCM with typical gait, dexterity, and sphincter symptoms that were only linked to DCM after 11 visits to the emergency department. 74 Oh et al 75 reported a patient with DCM in which a megacolon only resolved after surgical decompression of the cervical stenosis.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Kobayashi et al found that DCM patients reported chest tightness 22.9 times more often than non-myelopathic patients, 73 resulting in inclusion as one of the symptoms to be queried in an 8-item questionnaire for DCM screening. Mowforth et al 74 reported a patient with sensory dysesthesia, including facial dysesthesia secondary to DCM with typical gait, dexterity, and sphincter symptoms that were only linked to DCM after 11 visits to the emergency department. 74 Oh et al 75 reported a patient with DCM in which a megacolon only resolved after surgical decompression of the cervical stenosis.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%
“…Mowforth et al 74 reported a patient with sensory dysesthesia, including facial dysesthesia secondary to DCM with typical gait, dexterity, and sphincter symptoms that were only linked to DCM after 11 visits to the emergency department. 74 Oh et al 75 reported a patient with DCM in which a megacolon only resolved after surgical decompression of the cervical stenosis. 75 Houten et al reported a series of 12 DCM patients presenting without upper extremity symptoms 76 that all reported gait difficulty; more than half had objective lower extremity weakness.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%
“…We recently reported on an unusual case of sensory dysesthesia in DCM involving the body but also the face. 39 Our prevailing clinical view was that the facial symptoms represented a psychosomatic overlay but conceptualized that projections of the nucleus-tractus solitarius do project into the cervical spinal cord and altered trigeminal nerve processing was theoretically possible. Additionally, the emerging evidence of structural cerebral re-organization in response to myelopathy 40,41 questions whether there is associated altered central processing.…”
Section: Findings In Contextmentioning
confidence: 99%
“…18 There is a broad differential for DCM symptoms 19 and poor consensus on what the most common DCM symptoms are. In addition, an increasing number of less well-described symptoms such as dysaesthetic sensory symptoms, 6 chest tightness 20 and headache 21 are being reported. 22 Neurological examination findings include upper motor neuron signs in the upper and lower limbs: spasticity and hyperreflexia in addition to weakness.…”
Section: Why Assess Dcm Education?mentioning
confidence: 99%
“…Initially, patients with DCM are commonly seen by primary care, emergency and medical physicians. 6 7 These non-specialist triage points appear key to earlier diagnosis, yet DCM features poorly in medical curricula. 8 This risks non-specialist doctors being poorly equipped to detect DCM.…”
Section: Introductionmentioning
confidence: 99%